Factors related to the abandonment of Assistive Technology devices: a literature review (Human Factors in Design, 2023)
Assistive Technology (AT) resources and devices provide greater independence for people with disabilities, but many are abandoned or not used. The objective of this study was to know factors involved in the abandonment of AT devices. An integrative literature review was carried out, with searches for complete articles published in the last 5 years, in English or Portuguese, that addressed factors related to the abandonment or non-use of AT resources or devices by adults. The results indicate that factors such as the behavior of professionals, culture and design influence its use. Professionals who work in the AT area need to pay attention to the theme.
Keywords: Assistive Technology; Evaluation of Results of Therapeutic Interventions; People with Disabilities; Abandonment